DIFFERENCES IN STUDENTS' ABILITY TO RECEIVE AND PROCESS INFORMATION ON EDUCATIONAL STATISTICS COURSES - Shafira Zahra Nur Ghifari; Zahid Mubarok; Sutisna Sutisna (Universitas Labuhanbatu, 2023)
The ability to receive and process information is included in cognitive abilities. This ability is a basic ability that everyone should have well because almost every day human life is surrounded by information. However, not all individuals can immediately understand the information provided to them, including students. For this reason, this study aims to find out how students' abilities in receiving and processing information in educational statistics courses. In addition, it is also to find out what causes differences in students' abilities in receiving and processing information in educational statistics courses. The method used is a qualitative method with a grounded theory approach. Data collection was carried out by observing, filling out questionnaires, and documentation. The research was conducted in Class PAI 5E FAI UIKA Bogor. The results showed that student's ability to receive and process information in educational statistics courses was quite good. This can be seen from the results of student learning which shows that the average is at A-B grades. The causes of differences in student abilities in receiving and processing information on educational statistics courses are caused by 3 things, namely interest and motivation to learn, focus on learning, and supporting facilities in learning these courses.Keywords: cognitive ability; learning outcomes; educational statisticsÂ AbstrakKemampuan menerima dan mengolah informasi termasuk dalam kemampuan kognitif. Kemampuan ini merupakan kemampuan dasar yang seharusnya dimiliki setiap orang dengan baik karena hampir setiap hari kehidupan manusia dikelilingi dengan adanya informasi. Akan tetapi tidak semua individu bisa langsung memahami informasi yang diberikan kepada mereka termasuk mahasiswa. Untuk itu, penelitian ini bertujuan untuk mengetahui bagaimana kemampuan mahasiswa dalam menerima dan mengolah informasi mata kuliah statistika pendidikan. Selain itu juga untuk mengetahui apa penyebab perbedaan kemampuan mahasiswa dalam menerima dan mengolah informasi mata kuliah statistika pendidikan. Metode yang digunakan yaitu metode kualitatif dengan pendekatan grounded theory. Pengambilan data dilakukan dengan melakukan observasi, pengisian kuesioner, dan dokumentasi. Penelitian dilakukan di Kelas PAI 5E FAI UIKA Bogor. Hasil penelitian menunjukkan bahwa kemampuan mahasiswa dalam menerima dan mengolah informasi mata kuliah statistika pendidikan dapat dikatakan cukup baik. Hal ini dapat dilihat dari hasil belajar mahasiswa yang menunjukkan rata-rata berada pada nilai A-B. Adapun penyebab perbedaan kemampuan mahasiswa dalam menerima dan mengolah informasi mata kuliah statistika pendidikan disebabkan oleh 3 hal yaitu minat dan motivasi belajar, fokus belajar, serta fasilitas penunjang dalam pembelajaran mata kuliah tersebut.Kata kunci:Kemampuan kognitif, hasil belajar, statistika pendidikan